VOCABULARY LEARNING STRATEGIES OF THE SECOND-SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT TADULAKO UNIVERSITY - Devi Handayani; Nadrun Nadrun (Tadulako University, 2021)
This research aims to identify the strategies used and find out the effective strategies used by the second-semester students of English Education Study Program in learning vocabulary. This research applied qualitative research, especially case study. The participants were 20 students filling out the questionnaires and six students answering the interviews. The participants of this research were selected by using purposive sampling technique. The instruments of data collection were questionnaires and interviews. The data gathered were analyzed by google form and descriptively. The data analysis results show that most students always use an electronic dictionary to find out the meaning of a word in determination strategies. Next, in social strategies, most students prefer to interact with their friends through group discussion in class or asking the meaning of a new word. Then, in memory strategies, most students often remember a new word from its pronounced. In cognitive strategies, they often use context in the text to explain the meaning of a word. While, in metacognitive strategies, most students often use an English song to learn new words and watch videos related to the deep pronunciation of English. The effective strategies were watching videos or movies. Then, they often make new vocabulary notes to memorize the words and remember a new word when it is pronounced. They also use an electronic dictionary to find out the meaning of the word. In general, most second-semester students almost use all the strategies in the taxonomy of vocabulary learning strategies. The strategies most often used are using media, electronic dictionaries, interacting with other people, remembering new words when they are pronounced, and using context in the text to explain the new word's meaning.